2022
DOI: 10.3390/ijerph19127317
|View full text |Cite
|
Sign up to set email alerts
|

Associations between COVID-19 Pandemic, Lockdown Measures and Human Mobility: Longitudinal Evidence from 86 Countries

Abstract: Recognizing an urgent need to understand the dynamics of the pandemic’s severity, this longitudinal study is conducted to explore the evolution of complex relationships between the COVID-19 pandemic, lockdown measures, and social distancing patterns in a diverse set of 86 countries. Collecting data from multiple sources, a structural equation modeling (SEM) technique is applied to understand the interdependencies between independent variables, mediators, and dependent variables. Results show that lockdown and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 95 publications
3
18
0
Order By: Relevance
“…Similar results were obtained by Sun et al [43,44] for the world as a whole and by Linka et al [45,46] for European countries. Rahman and Thill [47] confirmed the patterns occurring based on studies on 86 countries. A higher number of confirmed COVID-19 cases and deaths reduced human mobility.…”
Section: Discussionsupporting
confidence: 73%
“…Similar results were obtained by Sun et al [43,44] for the world as a whole and by Linka et al [45,46] for European countries. Rahman and Thill [47] confirmed the patterns occurring based on studies on 86 countries. A higher number of confirmed COVID-19 cases and deaths reduced human mobility.…”
Section: Discussionsupporting
confidence: 73%
“… 20 In a study conducted in Indonesia, the most significant increase in SARS-CoV-2 cases was seen in the pharmacy and grocery sector, with 4.12%. 21 A large-scale study with data from 86 countries has shown that implementing lockdowns and reducing population mobility in workplaces, public transport, and retail-recreation sectors is very effective in preventing the spread of the epidemic. 21 In Turkey, after the Ramadan Feast at the end of May 2020, housing mobility decreased, and other activities increased, but cases and deaths remained relatively stable.…”
Section: Discussionmentioning
confidence: 99%
“… 21 A large-scale study with data from 86 countries has shown that implementing lockdowns and reducing population mobility in workplaces, public transport, and retail-recreation sectors is very effective in preventing the spread of the epidemic. 21 In Turkey, after the Ramadan Feast at the end of May 2020, housing mobility decreased, and other activities increased, but cases and deaths remained relatively stable. The fact that the increase in the number of cases and deaths was less than expected may have resulted from the mandatory mask application.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, walkability has become even more crucial considering the unprecedented effects of the Covid-19 pandemic on urban mobility ( Gargiulo et al, 2021;Hayrullaho ğlu and Varol, 2022;Rahman and Thill, 2022;Transport, 2022 ). In July 2020, the European Commission ( European Platform on Sustainable Urban Mobility Plans, 2020 ) provided ad hoc guidelines for implementing short-term transport planning interventions to face the current critical situation.…”
Section: Introductionmentioning
confidence: 99%